Practical SPECT/CT in nuclear medicine - Hogg, Peter; Seeram, Euclid (Springer London Imprint: Springer, 2013)
Nuclear Medicine is a diagnostic modality which aims to image and in some cases quantify physiological processes in the body to highlight disease or injury. Within nuclear medicine, over the past few decades, major technological changes have occurred and concomitantly changes in the knowledge and skills required have had to evolve. One of the most significant technological changes has been the fusion of imaging technologies, to create hybrid systems such as SPECT/CT, PET/CT and PET/MR. With these changes in mind, Practical SPECT/CT in Nuclear Medicine provides a handy and informative guide to the purchase, clinical implementation and routine use of a SPECT/CT scanner. Practical SPECT/CT in Nuclear Medicine will be a valuable resource for all personnel working in nuclear medicine and it will be of particular value to trainees.